Arduino-Based ECU Simulator and OBD-II Scanner for Electric Vehicle Diagnostics with CAN BUS - Tole Sutikno; Mulyadi; Son Ali Akbar; Tri Wahono (Jurnal Teknik Elektro, 2026)
Electric vehicles (EVs) require reliable and accurate diagnostic systems to ensure the performance, safety, and efficiency of their electrical and electronic components. This study presents the design and development of an Arduino-based Electronic Control Unit (ECU) simulator and an On-Board Diagnostics II (OBD-II) scanner for electric vehicle diagnostics, both using the Controller Area Network (CAN) communication protocol. The ECU simulator is built using an Arduino Mega 2560 and an MCP2515 CAN controller, equipped with potentiometers and push buttons to simulate various EV operating parameters such as motor speed, vehicle speed, battery voltage, temperature, state of charge, and regenerative braking conditions, as well as to generate Diagnostic Trouble Codes (DTCs). The OBD-II scanner is developed using an Arduino Uno, MCP2515 module, and a Nextion HMI LCD to support live data monitoring, DTC reading, and DTC clearing in accordance with SAE J1979 standards. System performance was evaluated using a CAN analyzer to verify frame structure, arbitration behaviors, data integrity, and communication reliability. The experimental results show that all transmitted CAN frames conform to the ISO 11898 standard and are correctly interpreted by the OBD-II scanner. The system achieved data accuracy of approximately 97% with an average response time of ±100 ms, indicating stable, reliable communication. The developed platform provides a low-cost, flexible, and effective solution for electric vehicle diagnostics, education, and laboratory testing without requiring real vehicles. It can serve as a foundation for future research involving multi-ECU communication and additional OBD protocols.